Du Conservatoire national des arts et métiers à la mission ethnographique Ogooué-Congo, et retour - Robert Nardone; Loïc Petitgirard; Catherine Radtka (Revue d’Histoire des Sciences Humaines)
Our focus here is the Conservatoire national des arts et métiers [CNAM] and André Didier, who was officially the ‘sound engineer’ during the Ogooué-Congo ethnographic expedition. We argue that his presence made the mission a success due to the collecting of material for ethnographic film-making and musicological study. Didier’s and the Conservatoire’s contribution is best approached through sound recording. In order to grasp the malleability of ‘sound’ as an object of study, and to analyse its presence and mobilisation in different professional milieus, we borrow the concept of ‘boundary object’ from Star and Griesemer (1989). This enables us to analyse the different interpretations of the sounds for which Didier was responsible. André Didier’s commitment is considered in the light of the formative institution, the CNAM, from which he came.